Enhancing Career Interest Assessment in South Africa: Lessons Learned From the Development of the South African Career Interest Inventory-IsiXhosa Version - Jansen van Vuuren, Nicola; Rabie, Stephan; Naidoo, Anthony Vernon (Frontiers in Psychology, 2022)
Career interest assessment is a vital component of career guidance and counselling. Ensuring fair assessment practice is, however, complex and challenging in a diverse cultural setting such as South Africa. A myriad of factors – including culture and language – may moderate individual performance on career interest assessments. For this reason, it is imperative to acknowledge these factors when developing career interest assessments in the South African context. Particular attention was paid to these issues of language and culture during the recent development of the South African Career Interest Inventory (SACII) and South African Career Interest Inventory-isiXhosa version (SACII-X). In this paper we discuss some of these crucial considerations that informed the conceptualization and development of the SACII-X. The promising reliability and validity demonstrated by these assessments, provide support for the use of career assessments based on imported career theories, if sensitivity is afforded to contextual-, language-, and cultural considerations during the development of assessment measures.